VD_FINDINFO Décision / 2014 / 1088 vom 11. Dezember 2014 - VD Tribunal cantonal (2014)
DÉTENTION PROVISOIRE, PROLONGATION, RISQUE DE RÉCIDIVE, SOUPÇON | 221 al. 1 let. c CPP (CH), 222 CPP (CH), 393 al. 1 let. c CPP (CH)